Cost of Manufacturing for Recombinant Snakebite Antivenoms - Jenkins, Timothy Patrick; Laustsen, Andreas Hougaard (Frontiers in Bioengineering and Biotechnology, 2020)
Snakebite envenoming is a neglected tropical disease that affects millions of people across the globe. It has been suggested that recombinant antivenoms based on mixtures of human monoclonal antibodies, which target key toxins of medically important snake venom, could present a promising avenue towards the reduction of morbidity and mortality of envenomated patients. However, since snakebite envenoming is a disease of poverty, it is pivotal that next-generation therapies are affordable to those most in need, which warrants analysis of the cost dynamics of recombinant antivenom manufacture. Therefore, we present, for the first time, a bottom-up analysis of the cost dynamics surrounding the production of future recombinant antivenoms based on available industry data. We unravel the potential impact that venom volume, abundance of medically relevant toxins in a venom, and the molecular weight of these toxins may have on the final product cost. Furthermore, we assess the roles that antibody molar mass, manufacturing and purification strategies, formulation, antibody efficacy, and potential cross-reactivity play in the complex cost dynamics of recombinant antivenom manufacture. Notably, according to our calculations, it appears that such next-generation antivenoms based on cocktails of monoclonal immunoglobulin Gs (IgGs) could be manufacturable at a comparable or lower cost to current plasma-derived antivenoms, which are priced at USD 13-1120 per treatment. We found that monovalent recombinant antivenoms based on IgGs could be manufactured for USD 20-225 per treatment, while more complex polyvalent recombinant antivenoms based on IgGs could be manufactured for USD 48-1354 per treatment. Finally, we investigated the prospective cost of manufacturing for recombinant antivenoms based on alternative protein scaffolds, such as DARPins and nanobodies, and highlight the potential utility of such scaffolds in the context of low-cost manufacturing. In conclusion, the development of recombinant antivenoms not only holds a promise for improving therapeutic parameters, such as safety and efficacy, but could possibly also lead to a more competetive cost of manufacture of antivenom products for patients worldwide.